PLANT GROWTH IN MICROGRAVITY FOR BLSS: GENERAL ISSUES AND THE ITALIAN CONTRIBUTION - Veronica De Micco; Carmen Arena; Stefania De Pascale; Giovanna Aronne (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Plants are among key organisms in Bioregenerative Life Support Systems (BLSSs) in Space because they have a role in the regeneration of resources and in the psychological support of the crew. The design of efficient BLSSs cannot be irrespective of the deep knowledge of the functioning of the vegetal systems under the effect of Space factors. Under an evolutionary perspective, reduced gravity can be considered one of the factors driving the evolution of plants in Space. In this paper, we outline the need for plant-based BLSSs to sustain exploratory-class manned missions in Space. After some evolutionary considerations about future plant development in Space, we also report a synthesis of the results of case studies performed by Italian research groups aiming to understand the effect of simulated or real microgravity on various aspects of plant growth and reproduction. We conclude emphasising how plant research in Space should be addressed to both improvement of the knowledge of basic biological processes and development of new agro-technologies. Efforts to have multidisciplinary approach to understand the effect of Space factors on plant growth are needed considering that such factors affect the biological systems contemporarily at molecular, biochemical, morphostructural and physiological levels.